Patients with rare autoimmune inflammatory disorders demonstrate sub-clinical left ventricular dysfunction. (14th October 2021) - Khanna, S; Wen, I; Gupta, A; Thakur, A; Bhat, A; Chen, H H L; Gan, G C H; Tan, T C
Abstract: Background: ANCA-associated Vasculitis (AAV) and inflammatory myositis (IM) are rare inflammatory autoimmune disorders mediated via pro-inflammatory cytokines and result in a systemic inflammatory state with multi-organ involvement. There is growing evidence to suggest cardiovascular involvement within these inflammatory states. Left ventricular global longitudinal strain (LV-GLS) is proposed to be a more sensitive measure of LV systolic function when compared to standard two-dimensional measures such as LV ejection fraction (LVEF). Purpose: The purpose of this study was to assess for subclinical cardiac dysfunction in these cohorts when compared to controls. Methods: Consecutive patients with AAV (n=56) and IM (n=68) admitted to our institution during 2013–2021 were assessed. Patients with pre-existing cardiovascular disease, significant renal impairment (eGFR <30mL/min/1.73m 2 ), LVEF <50% or lack of comprehensive transthoracic echocardiography during admission were excluded (n=72). LV-GLS was measured offline using vendor-independent software (TomTec Arena, Germany v4.6). Results: A total of 52 patients (22 AAV and 30 IM) were age- and gender-matched to 52 controls. In comparison of the two study populations (AAV and IM), patients with AAV had higher rates of renal impairment (p=0.02) but lower rates of interstitial lung disease when compared to IM (p=0.02). There were no differences between the two groups in terms of cardiovascular risk factors, demographics or other laboratory investigations (p>0.05 for all). In comparison to the control population, patients with AAV and IM had higher indexed LV mass and a lower TAPSE, respectively, when compared to controls. These cohorts also demonstrated impaired LV-GLS (−17.7±2.6 vs −20.6±2.4; p<0.01) when compared to healthy controls, despite no differences in LVEF (62.6±7.8 vs 61.8±5.4; p=0.56) between both groups. Conclusions: Our results suggest that patients with autoimmune inflammatory disorders demonstrate subclinical LV dysfunction which is likely secondary to a chronic inflammatory state. Funding Acknowledgement: Type of funding sources: None.